Comorbidity in patients with the diagnosis of Arterial Hypertension admitted to Internal Medicine wards - Kou Shunchao; Li Xueqing; Miguel Ángel Blanco Aspiazu; Jorge Bacallao Gallestey (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Comorbidity, as a problem in the practice of the medical profession, implies greater complexity in terms of diagnosis, treatment, creation of care protocols, and research. It is necessary to identify comorbidity in the hypertensive patient treated in internal medicine wards and establish etiopathogenic, pathophysiological, and therapeutic mechanisms. Objective: To identify the magnitude of comorbidity in patients with arterial hypertension admitted to the Internal Medicine wards. Material and Methods: A descriptive and prospective research was carried out on 144 hypertensive patients. The necessary information was collected from medical interviews, patients´ clinical exams, clinical histories, and case discussions with the doctors that were providing medical care to these patients.  The data obtained were recorded in the database of Statistical Package SPSS software version 11.5. Results: The most frequent comorbidities were type 2 diabetes mellitus in a 72.9%; ischemic heart disease in a 54.9%, and cerebrovascular disease in a 36.1%. Conclusions: The magnitude of comorbidity in hypertensive patients admitted to Internal Medicine Wards recognizes Type 2 Diabetes Mellitus and atherosclerotic complications derived from both entities, as the most relevant pathophysiological associations. Keywords: arterial hypertension, diabetes mellitus, comorbidity, internal medicine.